Automated Development of Clinical Strategies Using Multistage Decision Analysis - Glasziou, P. (Methods of Information in Medicine, 1986)
The development of investigative strategies by decision analysis has been achieved by explicitly drawing the decision tree, either by hand or on computer. This paper discusses the feasibility of automatically generating and analysing decision trees from a description of the investigations and the treatment problem. The investigation of cholestatic jaundice is used to illustrate the technique.Methods to decrease the number of calculations required are presented. It is shown that this method makes practical the simultaneous study of at least half a dozen investigations. However, some new problems arise due to the possible complexity of the resulting optimal strategy. If protocol errors and delays due to testing are considered, simpler strategies become desirable. Generation and assessment of these simpler strategies are discussed with examples.
Keywords: Decision Analysis; Investigative Strategy; Computer-aided Decision-Making; Clinical Algorithm; Cholestasis